Dual citizenship rights: do they make more and better citizens? - Francesca Mazzolari (Institute for the Study of Labor (IZA), 2007)
In the 1990s, Colombia, the Dominican Republic, Ecuador, Costa Rica and Brazil passed dual citizenship laws granting their expatriates the right to naturalize in the receiving country without losing their nationality of origin. I estimate the effects of these new laws on naturalization rates and labor market outcomes in the United States. Based on data from the 1990 and 2000 U.S. censuses, I find that immigrants recently granted dual nationality rights are more likely to naturalize. They also experience employment and earnings gains, together with drops in welfare use, suggesting that dual citizenship rights not only increase the propensity to naturalize but may also promote economic assimilation. The effects of dual citizenship on improved economic performance, if mediated through naturalization, are consistent with American citizenship conferring greater economic opportunities.
Keywords: 330; Migranten; Staatsangehörigkeit; Soziale Integration; Berufliche Integration; Hispano-Amerikaner; USA